2016
DOI: 10.1155/2016/4917387
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Approach of Tumor-Associated Inflammation in Mammary Cancer between Humans and Dogs

Abstract: Infiltrating cells of the immune system are widely accepted to be generic constituents of tumor microenvironment. It has been well established that the development of mammary cancer, both in humans and in dogs, is associated with alterations in numbers and functions of immune cells at the sites of tumor progression. These tumor infiltrating immune cells seem to exhibit exclusive phenotypic and functional characteristics and mammary cancer cells can take advantage of signaling molecules released by them. Cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 137 publications
(169 reference statements)
1
44
0
5
Order By: Relevance
“…Inflammation and oxidative damage have been associated with several tumours in humans and animals . Furthermore, development of an APP response and of oxidative stress were previously described in human breast cancer and in canine mammary tumours .…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Inflammation and oxidative damage have been associated with several tumours in humans and animals . Furthermore, development of an APP response and of oxidative stress were previously described in human breast cancer and in canine mammary tumours .…”
Section: Discussionmentioning
confidence: 81%
“…Inflammation and oxidative damage have been associated with several tumours in humans and animals. 8,41,42 Furthermore, development of an APP response and of oxidative stress were previously described in human breast cancer and in canine mammary tumours. [21][22][23][24][25][26] APP and parameters of oxidative status were also proved to be clinically useful biomarkers in feline oncologic diseases, [43][44][45] however, to the best of our knowledge, this is the first study to comprehensively evaluate the APP and the antioxidant responses of feline spontaneous malignant mammary tumours.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the majority of immune cells infiltrated in the canine mammary tissues were lymphocytes not neutrophils and macrophages (NGAL‐producing cells), which is somewhat consistent with previous reports. Carvalho et al reported that chronic inflammation is accompanied by various lymphocytic cells, such as T helper, regular T cells, and tumour‐associated M2 macrophages infiltrating into cancer tissues, which represents key elements for new microvessel formation, invasiveness and metastasis . Of note, when CMT samples with infiltration of neutrophils and macrophages were excluded (Figure A), the mean NGAL expression score in the group of normal, benign and malignant CMTs exhibited the same descending order as that noted without exclusion (Figure A).…”
Section: Discussionmentioning
confidence: 60%
“…Carvalho et al reported that chronic inflammation is accompanied by various lymphocytic cells, such as T helper, regular T cells, and tumour-associated M2 macrophages infiltrating into cancer tissues, which represents key elements for new microvessel formation, invasiveness and metastasis. 47,48 Of note, when CMT samples with infiltration of neutrophils and macrophages were excluded ( Figure 5A), the mean NGAL expression score in the group of normal, benign and malignant CMTs exhibited the same descending order as that noted without exclusion ( Figure 4A). This result indicates that inflammation status unlikely influences the expression of NGAL in CMTs, at least among the samples analysed in the present study.…”
Section: T a B L E 3 Analysis Of Inflammatory Cells Presented In Canimentioning
confidence: 67%
“…However, this procedure is not satisfactory in canids because of the complex morphology of cells mammary tumours (Dolka et al, 2018). The histopathology and immunohistochemistry are known to be sufficient to analyse cells morphology and glycoprotein markers on the canine mammary tumours (Carvalho et al, 2016). The correct diagnoses facilitate the clinicians to provide precision therapy.…”
Section: Introductionmentioning
confidence: 99%